2012
DOI: 10.1071/an11071
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide selection in poultry

Abstract: Abstract. In poultry breeding programs owned by private companies, selection is done within closed populations based on comprehensive phenotypic data recording in both pure and cross line birds under standardised housing conditions. Due to sex-limited data recording, male selection for egg quality and production traits is based mainly on female sibling tests. Early selection of the most promising male within full sib families will improve the rate of genetic progress and can substantially reduce the generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Although GS has the potential to be expensive, breeders have begun to implement various strategies to minimize the costs of genotyping and retraining. Higher accuracies can be obtained by combining data from populations with and without genomic data using single-step G-BLUP, and costs associated with large-scale genotyping can be reduced by imputing high-density genotypes from low-or reduced-density SNP chips (112). This method was demonstrated in a population of brown egg layers in which, after two generations of high-density genotyping of all parents, sires were high-density genotyped in generations three through five, and dams were either high-or reduced-density genotyped for one to two generations.…”
Section: Great Grandparentmentioning
confidence: 99%
“…Although GS has the potential to be expensive, breeders have begun to implement various strategies to minimize the costs of genotyping and retraining. Higher accuracies can be obtained by combining data from populations with and without genomic data using single-step G-BLUP, and costs associated with large-scale genotyping can be reduced by imputing high-density genotypes from low-or reduced-density SNP chips (112). This method was demonstrated in a population of brown egg layers in which, after two generations of high-density genotyping of all parents, sires were high-density genotyped in generations three through five, and dams were either high-or reduced-density genotyped for one to two generations.…”
Section: Great Grandparentmentioning
confidence: 99%
“…GS is being applied extensively for genetic improvement of dairy cattle and two major high density arrays (>500K) are now available for cattle (Rincon et al ., ). For chicken, several studies have reported the use of proprietary medium density arrays for GS in commercial broiler and layer breeds (Avendaño et al ., ; Dekkers JCM, ; Preisinger, ; Wolc et al ., ). For instance, the EW group of poultry breeding companies (including Aviagen Ltd., Hy‐Line International and Lohmann LTZ) developed a proprietary 42K Illumina iSelecta BeadChip for application to GS (Avendaño et al ., ).…”
Section: Microarray Resources In Chicken and Their Applicationsmentioning
confidence: 99%
“…In spite of all these resources no HD genotyping array is yet available for this species that can facilitate high throughput investigation of many individuals for research and commercial breeding. A number of studies, however, have reported the use of low to medium (3 K to 60 K) density panels for various purposes [4-7] but these panels were proprietary and have not been made available for wider use. In contrast, for cattle, for example, two HD genotyping arrays (both >600 K) are now available [8,9].…”
Section: Introductionmentioning
confidence: 99%